Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Opuść nawiasy i zredukuj wyrazy podobne 4.67 gwiazdek na podstawie 6 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Opuść nawiasy i zredukuj wyrazy podobne

1.1.
 Zadanie

1.2.
 Zadanie

`a) \ \ -(x^2-x)-(x+x^2)=-ul(x^2)+x-x-ul(x^2)=-2x^2`

`b) \ \ x^2-(x-(x^2-x-1))=x^2-(ulx-x^2+ulx+1)=x^2-(2x-x^2+1)=x^2-2x+x^2-1=2x^2-2x-1` 

`c) \ \ -(-(-x^3+x)+x^2)+x^3=` `-(x^3-x+x^2)+x^3=-ul(x^3)+x-x^2+ul(x^3)=x-x^2`

`d) \ \ 6x-(4y-(x-2y))-(2x-(y-x))=6x-(4y-x+2y)-(2x-y+x)=6x-(6y-x)-(3x-y)=` 

`=ul(6x)-6y+ulx-ul(3x)+y=4x-5y` 

`e) \ \ 4x^2-(y^2-2x^2)-(y^2-(-2y^2-x^2))=` `ul(4x^2)-y^2+ul(2x^2)-(ul(ul(y^2))+ul(ul(2y^2))+x^2)=` `6x^2-y^2-(3y^2+x^2)=` 

`=6x^2-ul(y^2)-ul(3y^2)-x^2=5x^2-4y^2`

`f) \ \ -(2xy+x^2y-3x^2y^2)+xy-(2x^2y^2-x^2)=-ul(2xy)-ul(ul(x^2y))+3x^2y^2+ul(xy)-2x^2y^2+ul(ul(x^2y))=`

`=-xy+x^2y^2`